UJI KUALITAS OBAT TRADISIONAL ANTIDIABETES DARI BUAH BUNCIS DAN BUAH PARE - Baiq Risni Maripa; Yayuk Andayani; Lalu Rudyat Telly Savalas (Jurnal Penelitian Pendidikan IPA, 2019)
This research was conducted to determine the quality of antidiabetic traditional medicines from beans and bitter melon after 6 months of storage. Beans and bitter melon contain bioactive compounds such as flavonoids, beta sitosterol, stigmasterol, alkaloids, saponins, and phenols which function as antidiabatic. However, environmental factors such as production processes, and environmental temperatures affect the storage process. So we need to test the quality of antidiabetic drugs after 6 months of storage. The tests are pH test, total plate number test, mold and yeast number test. Based on the test the following results are obtained. The pH obtained was 4.75, the plate number was 0.002 colonies / g, mold number and yeast 0.01 x103 colonies / g. Based on these results, the quality of antidiabetic traditional medicines from beans and bitter was kept in quality after 6 months of storageKeywords: Quality of storage, traditional medicine, beans, bitter melon